2017
DOI: 10.5539/jfr.v6n1p78
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Children’s Lunch Box Contents by Photograph and Their Relationship with Mothers’ Concern

Abstract: Japanese kindergarten children usually bring lunch prepared by mothers. The contents may be influenced by mothers' food concerns. We investigated the relationship between mothers' concerns and children's lunch box contents and preferences. Lunch boxes of 209 children were digitally photographed for 4 days at a private kindergarten in Japan. The amounts of rice, main dishes, vegetables and fruits in the lunch boxes were estimated by measuring the area occupied by each in the photograph; a questionnaire, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…Parental concern about adolescent weight was associated with lower intake of energy-dense snacks and less home availability of these food items (MacFarlane et al, 2010). In addition, our previous study suggested that the amount of vegetables in packed lunches may be related to mothers" concern for vegetables and children"s preferences (Osera et al, 2017b). The present study showed the same tendency as MacFarlane"s study and our previous study; the mother answered children"s high and low of non-cognitive skills toward food were significantly related to their lifestyle and food habits in children of all ages (Table 4).…”
Section: Discussionsupporting
confidence: 84%
“…Parental concern about adolescent weight was associated with lower intake of energy-dense snacks and less home availability of these food items (MacFarlane et al, 2010). In addition, our previous study suggested that the amount of vegetables in packed lunches may be related to mothers" concern for vegetables and children"s preferences (Osera et al, 2017b). The present study showed the same tendency as MacFarlane"s study and our previous study; the mother answered children"s high and low of non-cognitive skills toward food were significantly related to their lifestyle and food habits in children of all ages (Table 4).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, high daily intake of soybean products by children was shown to be influenced by their mother's concern and positive attitudes towards the food habits of their children (Osera et al, 2016). In another study, the proportion of vegetables in the lunch box was shown to be related to mother's concern related to consumption of an appropriate mix of foods by their children to the preferences of the children (Osera et al, 2017). In addition, the development of children's food preferences involves a complex interplay of innate, familial and environmental factors (Cook, 2004).…”
Section: Introductionmentioning
confidence: 96%